Spontaneous Twin Pregnancy in Premature Ovarian Failure (2008) - R, Anna Liza; R.Z, Alik,; Zainuddin, Ahmad Murad; I, Ghazali, (Malaysian Medical Association, 2008)
SUMMARY Premature Ovarian Failure (POF) is associated with subfertility. Despite efforts to induce ovulation, success rates are low. We report a case of POF spontaneously conceiving twins while on hormone replacement therapy. KEY WORDS: Premature ovarian failure, Twin pregnancy, Hormone replacement therapy